(untitled) (Journal of the College of Basic Education, 2025)
The research conducted on the development of city sizes and ranks within Diyala Governorate from 1997 to 2023 aims to uncover the imbalances within the region’s urban network and identify its dominant city, employing established laws and quantitative indicators. The findings reveal fluctuations in the growth and ranking of Diyala Governorate’s cities, with some advancing in size while others decline. Over the years (1997, 2009, 2023), cities were categorized into three groups, demonstrating through the application of the rank-size rule and the urban dominance index that Baqubah emerges as the primary urban center, exerting dominance in population size. Following suit, Muqdadiya maintains its position as the secondary urban hub throughout the period. Despite differences in city size order, the application of Jefferson’s law consistently designates the third-ranking city, initially Khalis in 1997, succeeded by Baladruz in both 2009 and 2023. Finally, the research offers proposals aimed at achieving a more balanced distribution of urban centers within Diyala Governorate.